1985
DOI: 10.1177/030089168507100402
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Breast Cancer Recurrences through Periodic follow-up - is it Useless?

Abstract: The authors report on a multicentric consecutive series of 1120 breast cancer first recurrences. Cases detected as subjectively asymptomatic thanks to periodic follow-up examinations are compared to cases detected as symptomatic. The relapse-free interval from primary treatment was shorter for asymptomatic recurrences, confirming that an earlier diagnosis was achieved in these cases. In spite of this diagnostic anticipation, median and actuarial survival from primary treatment did not differ when asymptomatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…physical examination, routine laboratory and/or radiological examinations) and have excluded a role for tumour markers (Adair et al, 1974;Bishop et al, 1979;Horton, 1984;Ciatto et al, 1985;Andreoli et al, 1987). Two recent trials (Dixon et al, 1993a and b) have shown a role for tumour markers in guiding therapy and in the monitoring of the response to treatment of metastatic breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…physical examination, routine laboratory and/or radiological examinations) and have excluded a role for tumour markers (Adair et al, 1974;Bishop et al, 1979;Horton, 1984;Ciatto et al, 1985;Andreoli et al, 1987). Two recent trials (Dixon et al, 1993a and b) have shown a role for tumour markers in guiding therapy and in the monitoring of the response to treatment of metastatic breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…In patients treated 'early', median survival from salvage treatment and from mastectomy was prolonged when compared with that of patients treated only after metastases were ascertained by radiological means. The prolongation of the former interval might be considered misleading and due to the beginning of salvage treatment 'early' (Horton, 1984;Ciatto et al, 1985;Tomin and Donogan, 1987;Rutgers et al, 1989;Del Turco et al, 1994;Givio, 1994). This is the so-called lead time bias.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For two of these six studies, the number of deaths among the patients with recurrences was not available [9,10]. For two studies, no (exact) P-value was available [11,12]. For two studies, the number of deaths among the patients with recurrences was not available, nor the (exact) P-value was available [13,14].…”
Section: Selection Of Papersmentioning
confidence: 99%